Protective Effect of Ethyl Pyruvate on Epididymal Sperm Characteristics, Oxidative Stress and Testosterone Level in Methotrexate Treated Mice - E Atashfaraz; F Farokhi; Gh Najafi (JRI, 2013)
Background: Methotrexate (MTX) is an anti-metabolite drug widely used in treatment of neoplastic disorders, rheumatoid arthritis and psoriasis. The ester derivative, ethyl pyruvate (EP) is stable in solution and should function as an antioxidant and energy precursor. This study was conducted to evaluate the protective role of EP on sperm parameters, testosterone level and malondialdehyde (MDA) production in mice treated with MTX. Methods: 32 adult male NMRI mice weighing 26±2 g were divided into 4 groups. Group 1 received 0.1 ml/mice/day of distilled water intraperitoneally for 30 days (ip). Group 2 was treated with methotrexate at a dose of 20 mg/kg once a week (ip) for 30 days. Group 3 was treated with ethyl pyruvate at a dose of 40 mg/kg/daily (ip) for 30 days. Group 4 was treated with methotrexate (20 mg/kg) once a week simultaneously with ethyl pyruvate 40 mg/kg for 30 days. The results were analyzed by one-way ANOVA. A p<0.05 was considered to be significant. Results: The results showed significant (p<0.05) decrease in sperm count and sperm motility as well as testosterone concentration while sperm with damaged DNA and MDA concentration in mice treated with MTX in comparison with control and MX+EP groups increased significantly (p<0.05). Instead, MTX+EP group caused partial amelioration in all parameters mentioned above. Conclusion: Based on the present study, it can be concluded that MTX induced toxicity in sperm parameters and serum level of testosterone and increased MDA level. EP with its antioxidant properties could be administrated during treatment with MTX due to its protective effects on sperm parameters, plasma testosterone levels and lipid peroxidation.
Keywords: Ethyl pyruvate, Malondialdehyde, Methotrexate, Mice, Spermatozoa, Testosterone